Design and Efficiency Enhancement of Klystron-Like Relativistic Backward Wave Oscillator With Triple Cavity Extractor - Verma P.; Thottappan M. (My University, 2025)
In this article, the design and investigation of an X -band klystron-like relativistic backward wave oscillator (KL-RBWO) are presented. The present design includes three extractor cavities at the output Section of KL-RBWO that has been studied for their beam-wave interaction behavior using a finite difference time domain (FDTD) based 3-D electromagnetic (EM) particle-in-cell (PIC) code. The three extractor cavities used in the downstream of KL-RBWO before the collector increased the overall efficiency of the device with a sharp increase in the axial electric field and current in the region. The PIC simulation of the present KL-RBWO predicted an RF power of ∼ 2.3 GW at ∼ 9.55 GHz with electronic efficiency of ∼ 60% for the developed electron beam current of ∼ 6.72 kA. A constant microwave generation was observed up to 270 ns under the external guiding magnetic field of 2.9 T. © 1963-2012 IEEE.